User Studies without End-users? Analysis of the Proxy-users Involvement in the Development of Digital Products - Silva, Pedro Victor de Sousa; Da Costa Nunes, Erik Henrique; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: Users participation is crucial for the creation of digital products that address their real needs. In some of these cases, the only available option to ensure that some form of user perspective is considered during the product development is count on proxy-users. Objective: This paper examines how research studies involving proxy-users are conducted in the development of digital products. Methodology: A dual methodological approach was employed: firstly, a tertiary study was conducted from a previous systematic literature review with 164 studies, and secondly, a survey with 69 professionals involved in the development of digital products. Results: The results of the tertiary study indicate that while proxy-user research employs common HCI methods, aspects such as methodological rigor, justification for excluding end users, and proxy-users’ familiarity with the target audience are often unclear. The survey revealed diverse information sources on the users needs and contexts mentioned by respondents, and the reasons for not involving end users. To summarize the research findings, this study presents a set of 10 recommendations for industry professionals and researchers when involving proxy-users in their studies.